Pengolahan Buah Naga menjadi Produk Pangan pada Kelompok Tani Nagari Simpang Sugiran, Kabupaten Lima Puluh Kota - Mimi Harni; Fidela Violalita; Ermiati Ermiati; Irwan Roza; Yenni Muchrida; Tety Desrita Handayani; Henny Fitri Yanti; Agustina Agustina (Warta Pengabdian Andalas, 2021)
Red dragon fruit is one of the agricultural commodities in Simpang Sugiran Village. Dragon fruit has many functions and properties for health. Based on monitoring in the field, farmers do not have the knowledge and skills in processing dragon fruit into various processed dragon fruit products to increase their selling value. In addition, the price of dragon fruit and farmer acceptance continues to decline while the number of farmers cultivating is increasing. The purpose of this activity was to increase community knowledge and skills in processing dragon fruit, and business management to increase the added value of dragon fruit cultivation. The results of community service activities indicated that the diversification of dragon fruit processing is one of the most effective ways to increase community income in the Simpang Sugiran village. Dragon fruit can be processed into various processed products using simple technology and can be done as a home industry. This community service activity can motivate and encourage the entrepreneurial spirit of the Farmer Group of Simpang Sugiran, Guguak Sub District, Lima Puluh Kota, West Sumatra.